William Godwin : a political life - Thomas, Richard Gough (Pluto Press, 2019)
A biography of the early anarchist whose life and work was at the heart of British Radicalism.
Keywords: Godwin, William, -- 1756-1836 -- Philosophy.; Godwin, William, -- 1756-1836; Anarchistes -- Grande-Bretagne -- Biographies.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; Philosophy; Biographies; Biographies.